A capture-recapture study of the prevalence and implications of opiate use in Dublin - COMISKEY, CATHERINE; Barry, Joe M. (My University, 2001)
Background: To date there have been no studies estimating the hidden prevalence of opiate use in Dublin. Methods: A muftisource enumeration followed by the application of the capture-recapture method with log-linear modelling including age and gender stratification to remove heterogeneity was implemented to provide an estimate of the unknown size of the opiate-using population. Two medical and one legal data sources were used. Results: It was found that the ratio of known to unknown opiate users was 1:1.15 with a total of 13,460 (95% Cl: 12,037–15,306) users estimated in Dublin In 1996. Conclusion: The findings of this study have important ramifications for service delivery.
PUBLISHED
Keywords: Capture-recapture; Opiates; Prevalence; Heterogeneity; Delivery of health care; Gender; Stratification; Substance abuse